The public government communication between practice and theory - Cheikh, Fatima Zohra; Mohamed, Bergane (International journal of economic perspectives, 2025)
Public communication today is experiencing significant growth and expansion, with a growing interest in engaging with this emerging scientific field. Many governments have embraced it, and in recent years, it has attracted considerable attention from researchers who have focused—either implicitly or explicitly—on public communication as a domain closer to practice than to academic studies. This inclination aligns with the French approach, as clarified by Dominique Bessières, who argues that public communication is primarily a practice before it is a theoretical concept. The difference in classifying it within the political or public sphere stems from the theoretical fluctuations and the academic limitations of public communication, or its status as a scientific field based on various disciplines. These disciplines shape it as a domain for both research and active practice, a concept emphasized by the University of Laval in Canada. This article aims to shed light on the historical context of public communication—if it is indeed possible to document such history—between its practical application and its scientific field. The intention is to offer a simple, yet illuminating, perspective on the broader framework of public communication as it pertains to government and public spheres.